Evaluation of Production, Boron and Flavonoid Content of Shallot in the Lowlands Through the Application of Boron and Benzyl Amino Purine - Anas Muhtarom Kusriarmin; Yaya Hasanah; Diana Sofia Hanafiah; Nursa'adah; Hamidah Hanum (Indonesian Journal of Agricultural Research, 2024)
Boron is a micro nutrient that plays a role in strengthening cell walls, increase growth and production of shallot optimally. Benzyl amino purine (BAP) is a synthetic cytokinin that responds to plant growth and development, regulates flowering, and stimulates cell division of shallot. This research aims to identify the production and content of boron in shallots. The study was conducted in the lowlands and a factorial randomized block design was used. Boron (0, 2, 4, and 6 kg boric acid/ha) was used as the first factor and BAP (0, 100, and 200 ppm) was used as the second factor. The research used Bima Brebes as shallot variety. The research result showed that boron application of 2 kg boric acid/ha increased the number of tillers, fresh weight of shallot bulb and flavonoid content. Application of 200 ppm of BAP increased significantly the number of tiller. In view of aftereffects of the orthogonal polynomial and regression tests, it was found that the optimum Boron dose 2.695 kg of boric acid/ha produced the highest dry weight of shallot 23.661 g, the dry weight of shallot bulbs increased by 14.23% compared to without Boron application.